Mechanical and fracture properties of cellulose-fibre-reinforced epoxy laminates - Low, I.M.; McGrath, M.; Lawrence, D.; Schmidt, P.; Lane, J.; Latella, B.A.; Sim, K.S. (ELSEVIER SCI LTD, 2007)
Epoxy laminates reinforced with cellulose-fibre mats (CFM) have been synthesized and characterized. The influence of CFM dispersion on the mechanical and fracture properties of these laminates have been characterized in terms of elastic modulus, hardness, flexural strength, fracture toughness, indentation responses, impact-fracture, crack-growth resistance and in situ fracture. The reinforcement by the CFM resulted in a significant increase in the strain at break, indentation creep, fracture toughness and impact toughness but moderate increase in flexural strength and flexural modulus. A pronounced R-curve behaviour is exhibited by the CFNI-reinforced epoxy sample, which failed in a graceful manner with slow and stable crack-growth. The micromechanisms of toughening and crack-tip failure processes are identified and discussed in the light of observed microstructures from in situ and ex situ fracture. The implications for new approaches in the 'eco-design' of environmentally friendly composite materials are addressed. (c) 2006 Elsevier Ltd. All rights reserved.